NIPPLE DISCHARGE - T. N. Bukharova; N. V. Kandayeva; O. N. Panina (ABV-press, 2014)
According to the data available in the literature, as high as 50% of women have benign breast tumors frequently accompanied by nip- ple discharge. Nipple discharge may be serous, bloody, purulent, and colostric. The most common causes are breast abscess, injury, drugs, prolactinoma, intraductal pappiloma, ductal ectasia, intraductal cancer (not more than 10%).